Research and implementation of order-oriented textile production scheduling system. (19th May 2023) - Ding, Heng; Gao, Haoyu; Dong, Yude; Huang, Suyun
ABSTRACT: A production planning and scheduling system for small and medium-sized textile enterprises is designed according to the actual needs of textile enterprises in the process of informatization construction. The system considers orders as the primary focus and employs modular design ideas to design functional modules and standardized interfaces based on a three-tier architecture. Furthermore, it uses a database structure design and computer programming to ensure the efficiency and reliability of information services. The main functions of the system include prioritization, automatic production scheduling, order processing, and real-time monitoring of the machine. An analytical hierarchy process optimization method is proposed and applied to a textile enterprise. The running results reveal that this method can effectively reduce the order completion time, improve punctuality delivery rate, save 2–3 days of production planning and machine scheduling for the enterprise, improve the resource allocation ability and production management efficiency, and has guiding significance for small- and medium-sized textile enterprises to realize informatization.